Do not fear them: Reconsidering the objective of the Epistle of Jeremiah - Cizek, Paul (Journal for the study of the pseudepigrapha, 2025)
Idolatry is the ultimate concern of the pseudepigraphic Epistle of Jeremiah (Baruch 6). Correspondingly, some have argued that the author of the epistle aimed to disparage idolatry, while others have argued that the author composed the epistle to dissuade Jews from worshipping false gods. While these theses have some merit, I contend that the author did not target the ultimate concern of idolatry head on but rather the penultimate concern, namely the fear of idols, which the author conceptualized as a precursor to idol worship. Accordingly, I demonstrate how the epistle’s opening address (vv. 1–6), repetitive refrains, and individual strophes reveal the author’s focus on assuaging the fear of idols. The study not only refines our understanding of the author’s objective in composing the epistle, but makes the often-noted satirical nature of the strophes all the more fitting, to the extent that humor can be an antidote to fear.